The Link between Major Depressive Disorder & Chronic Coronary Syndrome - A Literature Review - Anwar, AFM Azim; Rahaman, Sheikh Nashfiqur; Mumu, Sanjida Anjum; Khaled, Md Fakhrul Islam; Ahmed, Khurshed; Hoque, Md Harisul (University Heart Journal, 2023)
Depression is prevalent among patients with coronary artery disease and has significant consequences. Occurrence of depression after a new diagnosis of stable angina is common and affects nearly 1 in 5 individuals. There have been several biological mechanisms by which depression may be related to coronary artery disease. As compared with nondepressed patients, those with depression have increased catecholamine levels,elevated resting heart rate, and decreased heart rate variability. . Behavioral characteristics of patients with depression include poor medication adherence, lower exercise tolerance,physical inactivity, poor dietary habits,and tobacco use. Although depression and its impact have been well documented in post-MI patients, much less is known about its significance in patients with chronic coronary syndrome(CCS).Despite the fact that CCS is the most common manifestation of coronary artery disease,sothere is a huge gap in the field of knowledge correlating CCS and depression. University Heart Journal 2023; 19(1): 26-30